2019
DOI: 10.1136/emermed-2018-207892
|View full text |Cite
|
Sign up to set email alerts
|

Combined nitrous oxide 70% with intranasal fentanyl for procedural analgosedation in children: a prospective, randomised, double-blind, placebo-controlled trial

Abstract: ObjectiveNitrous oxide 70% (N2O 70%) is an excellent medication for procedural analgosedation (PAS), yet the limit of its analgesic power remains uncertain; therefore, a combination with intranasal fentanyl (INF) was suggested. However, this combination seems to result in a higher rate of vomiting and deeper sedation. This study aimed at assessing the analgesic efficacy, sedation depth and rate of adverse events of PAS with N2O 70% with and without INF.MethodsPatients aged 2–16 years who qualified for PAS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…6 The risk of emesis for co-administered intranasal fentanyl with N 2 O was reported to be 10-27.5%, with increased rates at 70% N 2 O. 3,7 In our study, the emesis rate was 1.4% with N 2 O alone, and 3.7% (2/54) for intranasal fentanyl with N 2 O. This is also lower than the emesis rates (8.4%) with IM ketamine sedation reported.…”
contrasting
confidence: 53%
“…6 The risk of emesis for co-administered intranasal fentanyl with N 2 O was reported to be 10-27.5%, with increased rates at 70% N 2 O. 3,7 In our study, the emesis rate was 1.4% with N 2 O alone, and 3.7% (2/54) for intranasal fentanyl with N 2 O. This is also lower than the emesis rates (8.4%) with IM ketamine sedation reported.…”
contrasting
confidence: 53%
“…In 2019, Seiler et al (28) proved that there were no differences with regard to the analgesic efficacy, sedation depth and rate of AE of procedural analgo-sedation (PAS) in patients treated with N 2 O 70% with and without IN fentanyl.…”
Section: Fentanylmentioning
confidence: 99%
“…In these settings, no safety concerns were reported and IN fentanyl was found to be effective for early pain relief. Numerous studies have demonstrated the safety and efficacy of IN fentanyl in physician-directed protocols, including procedural sedation ( 8 , 9 , 13 , 14 ). However, previous studies reported data limited to children >3 years.…”
Section: Discussionmentioning
confidence: 99%